ANALISIS ASET LANCAR DAN TIDAK LACAR PADA PT MAHKOTA GROUP Tbk - Rifkawati, Rifkawati; Pasaribu, Deby Siska Oktavia; Theodora, Eka (MTU PRESS, 2025)
Analysis of current and non-current assets at PT. Mahkota Group Tbk. Based on the results of the research and discussion that have been presented previously, it can be concluded from the research regarding the analysis of current assets and non-current assets of PT. Mahkota Group Tbk. Current Assets Assets are the amount of money stated on the economic resources owned by the company, whether in the form of money, goods and rights guaranteed by law or certain parties arising from transactions or events in the past. How the company can be input on how the results of the analysis of current assets and non-current assets at PT. Mahkota Group Tbk. For the author, it can add knowledge and insight about matters related to the analysis of current assets and non-current assets. For further researchers, it can be a source of reference and contribution in terms of the analysis of current assets and non-current assets.